Brain tissue gadolinium retention in pediatric patients after contrast-enhanced magnetic resonance exams: pathological confirmation. - Stanescu, A. Luana; Shaw, Dennis W.; Murata, Nozomu; Murata, Kiyoko; Rutledge, Joe C.; Maloney, Ezekiel; Maravilla, Kenneth R. (Pediatric Radiology, 2020)
Background: Retained gadolinium from gadolinium-based contrast agents (GBCAs) used in MR exams has been inferred based on signal changes on serial brain MRI and subsequently demonstrated pathologically in adults. Retention has been similarly inferred in children but pathological demonstration in pediatric patients is limited. The long-term effects of retained gadolinium are unknown but are potentially of greater concern in children given their increased vulnerability from continuing development and their expected longer period of exposure. Several factors can influence gadolinium retention. In adults as well as in children, greater accumulation has been demonstrated based on MR signal changes with linear compared with macrocyclic gadolinium chelates, attributed to lower chelate affinity with linear agents. Effects of age at exposure on retention are unknown, while differences in GBCA washout rates are still under investigation and might affect gadolinium retention relative to time of GBCA administration.Objective: The purpose of this study was to confirm whether gadolinium brain deposits are present in pediatric patients who received GBCAs and to quantify the amounts present.Materials and Methods: Brain autopsy specimens from 10 pediatric patients between 1 year and 13 years of age who underwent at least one contrast-enhanced MR exam were analyzed for elemental gadolinium using inductively coupled plasma mass spectrometry. Brain samples included white matter, basal ganglia (putamen, globus pallidus), thalamus, dentate nucleus and tumor tissue as available. Type and dose of contrast agent, number and timing of contrast-enhanced MR exams and renal function (estimated glomerular filtration rate [eGFR]) were documented for each child.Results: Patient exposures ranged from 1 dose to 20 doses of GBCAs including both macrocyclic and linear ionic agents. Gadolinium was found to be present in brain tissue in all children and was generally highest in the globus pallidus. Those who received only macrocyclic agents showed lower levels of gadolinium retention.Conclusion: This study demonstrates pathological confirmation of gadolinium retention in brain tissue of a series of pediatric patients exposed to GBCAs including not only linear ionic agents but also macrocyclic agents with both nonionic and ionic compounds. The distribution and deposition levels in this small pediatric population are comparable with the findings in adults. While the clinical significance of these deposits remains unknown, at this point it would be prudent to exert caution and avoid unnecessary use of GBCAs in pediatric patients.